Novel indeno[1, 2-b]indole-spirofluorene donor block for efficient sensitizers in dye-sensitized solar cells. (April 2020) - Dai, Pan-Pan; Zhu, Yi-Zhou; Liu, Qing-Long; Yan, Yi-Qiao; Zheng, Jian-Yu
Abstract: Indeno[1, 2- b ]indole-spirofluorene (IISF) unit has been synthesized and firstly applied as a donor candidate for the sensitizer of dye-sensitized solar cells. Two new dyes JY57 and JY58, based on IISF donor, are consequently constructed, together with dithieno[3, 2- b :2′, 3′- d ]pyrrole (DTP) as π-bridge and cyanoacrylic acid as acceptor. For JY58, additional electron-withdrawing 2, 1, 3-benzothiadiazole unit is inserted between IISF donor and DTP π-bridge to achieve a broader absorption range. Both dyes show high J SC and good device performance in iodine electrolyte. The photovoltaic properties are further tuned by co-adsorption and co-sensitization strategies, and better PCEs are obtained. Among the series of cells under AM 1.5G irradiation, cells fabricated by the synergic adsorption of JY57, chenodeoxycholic acid and JY59, achieve the highest PCE of 9.56%, which is much higher than 8.46% for N719 at the same condition. Graphical abstract: Image 1 Highlights: Indeno [1, 2- b ]indole-spirofluorene (IISF) unit was firstly applied as donor in DSSCs. Dyes based on IISF show high J SC and good device performance in iodine electrolyte. The PCE is up to 9.56% based on cells with synergic effect of JY57, CDCA and JY59.